Correlation Between Silat Training and Motor Skill Improvement in Elementary School Children - Pedomanta Keliat; Brema Pehulisa Pandia; Boisandi Buulolo; Arjuna Arjuna; Aris Simaremare; Yupiter Prakasa Laia; Akbar Alvian Sitorus; Lasdo Pangihutan Sihombing; Cristeven Tono Situmorang; Fans Darno Prianto Osra Zalukhu (Joska: Jurnal Isori Kampar, 2024)
Objectives: This study investigated the correlation between traditional Silat training and motor skill development in elementary school children aged 7-12 years in Medan, Indonesia. Methods: A cross-sectional study was conducted with 120 elementary school students from three schools in Medan city. Participants were divided into two groups: Silat practitioners (n=60) with minimum 6 months training experience, and control group (n=60) with no martial arts background. Motor skills were assessed using the Test of Gross Motor Development-3 (TGMD-3) and Bruininks-Oseretsky Test of Motor Proficiency-2 (BOT-2). Data analysis was performed using SPSS version 28.0. Results: Silat practitioners demonstrated significantly higher motor skill scores compared to the control group (p<0.001). Strong positive correlations were found between training duration and gross motor skills (r=0.78, p<0.001), fine motor skills (r=0.65, p<0.001), and overall motor proficiency (r=0.82, p<0.001). The Silat group showed superior performance in balance (18.4±2.1 vs 14.2±2.8), coordination (19.6±1.9 vs 15.3±2.4), and bilateral coordination (17.8±2.3 vs 13.9±2.7). Conclusion: Traditional Silat training shows strong positive correlation with enhanced motor skill development in elementary school children, suggesting its potential as an effective physical education intervention for improving fundamental movement skills.